2019
DOI: 10.1186/s12879-019-4253-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices on schistosomiasis and soil-transmitted helminths among caregivers in Ingwavuma area in uMkhanyakude district, South Africa

Abstract: Background Schistosomiasis and soil-transmitted helminth infections are among the most chronic infections worldwide. Based on their demonstrable impact on human health, the WHO recently recommended the implementation of robust strategies aimed at controlling or eliminating schistosomiasis and soil-transmitted helminths by 2020. The implementation of this strategy, however, warrants a clear understanding of the community’s knowledge, attitudes and practices in relation to these infections. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 40 publications
5
29
0
Order By: Relevance
“…Our study shows that specific knowledge on the transmission, symptoms, and complications of STH infections are significantly associated with PC practice of PSACwhich is similar to findings in Ile-Ife, Nigeria [32], Ibadan, Nigeria [33], Jimma, Ethiopia [34] and KwaZulu-Natal, South Africa [35]. Although the overwhelming majority of mothers in our study are familiar with STH, during visits to health facilities are the only health education opportunities many mothers in this setting have.…”
Section: Discussionsupporting
confidence: 85%
“…Our study shows that specific knowledge on the transmission, symptoms, and complications of STH infections are significantly associated with PC practice of PSACwhich is similar to findings in Ile-Ife, Nigeria [32], Ibadan, Nigeria [33], Jimma, Ethiopia [34] and KwaZulu-Natal, South Africa [35]. Although the overwhelming majority of mothers in our study are familiar with STH, during visits to health facilities are the only health education opportunities many mothers in this setting have.…”
Section: Discussionsupporting
confidence: 85%
“…Multivariable analysis revealed that odds of STHs were 2.08 times higher in Schoolchildren who have inadequate knowledge as compared to those who have adequate knowledge about STHs. Similar findings reported from studies conducted in Wondo Genet district, Southern Ethiopia [39]. This might be attributed to the fact that schoolchildren who have good knowledge about the STHs are more likely to understand the mode of transmission and methods of prevention.…”
Section: Discussionsupporting
confidence: 83%
“…It is obvious from our study that communities situated beside dams usually have the tendency to be more exposed to urinary schistosomiasis because of changes in ecological settings that lead to increase in intermediate snail host which harbor infection and enhance transmission. Moreover, such communities tend to actively engage in water contact activities [2,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%